The Role of SWOT Analysis in Improving HR Effectiveness and Employee Performance Case Study: CV 06 Production - Miranda Astari; Yusleli Herawati; Hadi Jauhari (Takaza Innovatix Labs Ltd., 2026)
This study aims to analyze the implementation of human resource management (HRM) and its impact on employee performance at CV. 06 Production, using a SWOT analysis as an evaluation tool. The research approach used was descriptive qualitative, with data collection methods including in-depth interviews, documentation, and direct observation of event implementation by the internal team. The results indicate that internal strengths such as team competence, effective communication, and prompt problem-solving significantly support employee performance. However, weaknesses in the organizational structure exist, such as the lack of a dedicated HR division and a nonstandardized performance appraisal system. The SWOT analysis indicates that employee performance development strategies can be improved through the establishment of an objective indicator-based evaluation system and the enhancement of transparent and continuous training. Therefore, improvements in HRM implementation will increase teamwork effectiveness in every event project undertaken by CV. 06 Production.